An Evaluation on the Uncertainty for the Routine of Dosimetry Calibration at the National Secondary Standard Dosimetry Laboratory, Albania - Klotilda Nikaj (International Journal of Nuclear Security, 2025)
Every employer must, in relation to any work with ionizing radiation that they undertake, take all necessary steps to restrict so far as is reasonably practicable the extent to which their employees and other persons are exposed to ionizing radiation. This goal leads to an increased awareness about the proper maintenance and annual calibration of the personal dosimeters to ensure an accurate and precise radiation dose. The present work has described the performance of the radiation system of the 137Cs source at the National Secondary Standard Dosimetry Laboratory (SSDL), located at the Institute of Applied Nuclear Physics at the University of Tirana. This work also aims to analyze the performance of the most-used thermoluminescent dosimeter (TLD) in the institutions in the country in accordance with the custody, maintenance, and development of the Albanian national standards together with the provision of calibration services offered by SSDL related to these standards. After analyzing the overall performance of the TLDs, we can conclude that to reduce errors and minimize uncertainty, in personal dosimetry, we must check the performance of TLDs in terms of sensitivity, linearity, and calibration coefficients, as stated by the technical standards of radiation protection.
Keywords: dosimetry; analyzing; calibration; maintenance